2007
DOI: 10.1002/jbm.a.31195
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyclodextrins on the proliferation of HaCaT keratinocytes in vitro

Abstract: Safety and efficacy of pharmaceutical agents can be greatly improved by encapsulation within, or covalent attachment to, a biomaterial carrier. Drug delivery systems must deliver the necessary amount of drug to the targeted site for a necessary period of time, both efficiently and precisely. Various kinds of high-performance biomaterials are being constantly developed for this purpose. Cyclodextrins are potential candidates for such a role, because of their ability to alter physical, chemical, and biological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 62 publications
4
8
0
Order By: Relevance
“…7 ). These results confirmed the negative effect of high concentrations of ␤ -cyclodextrin as found in the proliferation assay as well as the LDH measurements for the biocompatibility study on ␤ -cyclodextrin [10] .…”
Section: Measurement Of Biocompatibility and Cytotoxicitysupporting
confidence: 75%
See 2 more Smart Citations
“…7 ). These results confirmed the negative effect of high concentrations of ␤ -cyclodextrin as found in the proliferation assay as well as the LDH measurements for the biocompatibility study on ␤ -cyclodextrin [10] .…”
Section: Measurement Of Biocompatibility and Cytotoxicitysupporting
confidence: 75%
“…This method is quick and easily adaptable for different types of cells and test conditions, but the assay is sensitive to interference from compounds with inherent LDH activity like serum-supplemented culture media. Using ATP and LDH measurement, our group has been able to further explore the cytotoxic influence of ␤ -cyclodextrin in concentrations of 0.5 and 1% (w/v) on HaCaT cells [10] . A significant increase in LDH release was found that accompanied the rapid decline of cell viability ( fig.…”
Section: Measurement Of Biocompatibility and Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…61 In our study, low cell toxicities were observed in all the three cell lines for cells treated with polymer extracts. The percentage cytotoxicity for cells treated from 24-72 hours did not vary significantly (P .…”
Section: In Vitro Biocompatibility Of Polymeric Microneedlessupporting
confidence: 49%
“…Previously, exposure of HaCaT cells to me ␤ -CD was shown to cause i ) a leakage of lactate dehydrogenase, ii ) an increase in caspase-3/7 activity, iii ) a decrease of ROS concentration, and iv ) an increase in interleukin 6 and 8 ( 35 ). In addition, inhibitory effects, such as inhibition of cell growth and cell cycle arrest, have been reported for various cell types ( 36,37 ).…”
Section: Transport Of Ps To Mitochondriamentioning
confidence: 99%